2020
DOI: 10.1101/2020.01.27.917567
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contrasting Effects of Western vs. Mediterranean Diets on Monocyte Inflammatory Gene Expression and Social Behavior in a Primate Model

Abstract: 23Summary 24Monocytes and macrophages-important mediators of innate immunity, health, and disease-are 25 sensitive to diet and stress. Western diets promote inflammation and disease, while 26Mediterranean diets reduce inflammation and promote health, although the mechanisms through 27 which diet alters immune function are unknown. Here, we conducted the first randomized, long-28 term diet trial in which macaques were fed either a Western-or Mediterranean-like diet to 29 determine how diet and behavior interact… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…The biological mechanisms underlying increased GM volume and cortical thickening require further study; however, they may reflect neuroinflammatory responses, as increases in GM volumes [49] and cortical thickening [50] have been associated with neuroinflammation in recent clinical studies. Western diets are pro-inflammatory [11,51], and we previously reported that circulating monocytes isolated from the Western group had pro-inflammatory gene expression profiles relative to those from the Mediterranean group [52]. We also reported that the Western group had lower rates of affiliation and social integration and higher rates of anxiety and social isolation than the Mediterranean group, suggesting that diet impacted the brain [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological mechanisms underlying increased GM volume and cortical thickening require further study; however, they may reflect neuroinflammatory responses, as increases in GM volumes [49] and cortical thickening [50] have been associated with neuroinflammation in recent clinical studies. Western diets are pro-inflammatory [11,51], and we previously reported that circulating monocytes isolated from the Western group had pro-inflammatory gene expression profiles relative to those from the Mediterranean group [52]. We also reported that the Western group had lower rates of affiliation and social integration and higher rates of anxiety and social isolation than the Mediterranean group, suggesting that diet impacted the brain [52].…”
Section: Discussionmentioning
confidence: 99%
“…Western diets are pro-inflammatory [11,51], and we previously reported that circulating monocytes isolated from the Western group had pro-inflammatory gene expression profiles relative to those from the Mediterranean group [52]. We also reported that the Western group had lower rates of affiliation and social integration and higher rates of anxiety and social isolation than the Mediterranean group, suggesting that diet impacted the brain [52]. Importantly, social isolation and anxiety are risk factors for dementia [53].…”
Section: Discussionmentioning
confidence: 99%